Syllabification of Lithuanian in terms of the Optimality Theory - Kazlauskienė, Asta (Baltistica, 2022)
The aim of this study is to explain the syllabification tendencies of language users based on the Optimality Theory. These tendencies do not coincide with the theoretically formulated Maximum Onset Principle. According to the Optimality Theory, speaking is based on constraints and their satisfaction. Faithfulness (the underlying form, or the input, and the surface form, or the output, must match) and markedness (marked forms should be used as little as possible) constraints can be distinguished. They are universal and characterized by hierarchy. The rankings of constraints depend on the language. In order to describe syllables, two faithfulness (Faith) constraints are important: Dep[endency] (each surface form must have an underlying representation) and Max[imality] (each underlying form must have a surface equivalent). In Lithuanian, these constraints are strictly observed: no sounds can be added or deleted. Consequently, the constraints of faithfulness must occupy a high position in the hierarchy of constraints. With the aim of examining a syllable, the following universal markedness constraints must be distinguished: Nucleus (syllables must have nuclei; this constraint is strictly observed in Lithuanian), Onset (syllables must have onsets), NoCoda (syllables must have no codas), *Complex-Onset (onsets must be non-complex) and *Complex-Coda (codas must be non-complex). The study has revealed that the constraint Align[ment]-Morph[eme]-L[eft] should be included in the description of the Lithuanian language (the consonants of the beginning of the root and the syllable must match), and in some cases Son[onority] may also be relevant (the new syllable must begin with a less sonorant sound). The research leads to the conclusion that in Lithuanian the syllable constraints are arranged in the following order of decreasing importance (ranking): Nucleus ≫ Faith ≫ Onset ≫ Align-Morph-L ≫ *Complex-Onset ≫ Nocoda ≫ *Complex-Coda. This constraint rating determines the syllabification of words, as in /mʲiːsʲ.lʲeː/ (En. riddle), /moːks.lɐs/ (En. science), / ɐŋksʲ.tʲɪ/ (En. early), etc.